Resin composition

A modified silicone resin and filler-based resin composition addresses the toxicity and strength issues of existing concrete protection methods, offering a safer and more robust coating film with enhanced strength and elongation.

JP2025000852AActive Publication Date: 2025-01-07DENKA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024170499
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-10-09
Filing Date
2024-09-30
Publication Date
2025-01-07
Estimated Expiration
2041-10-08

AI Technical Summary

Technical Problem

Existing resin compositions for concrete protection methods face issues due to the toxicity of isocyanurate compounds and low strength or followability of urethane and epoxy materials, necessitating a safer and more robust alternative.

Method used

A resin composition comprising a modified silicone resin and a filler, with specific properties such as maximum stress, breaking strain, and elastic modulus, to form a coating film with enhanced strength and elongation.

Benefits of technology

The resin composition provides a less harmful coating film with improved strength and elongation, effectively preventing concrete flaking and dripping, and passing various tests like punch-out and crack followability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000852000001_ABST
    Figure 2025000852000001_ABST
Patent Text Reader

Abstract

To provide a resin composition for a concrete surface-protective construction method containing no isocyanurate compound, low in hazardousness, and excellent in strength and elongation.SOLUTION: A resin composition includes a modified silicone resin and a filler, where the maximum stress is 5.0 N / mm2 or more, a fracture strain is 100% or more, and an elastic modulus is 2.0 MPa or more when measured in accordance with JIS K 6251 in a cured product of the resin composition cured at 23°C and a relative humidity of 50% for 7 days.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, and more particularly to a resin composition used in a surface protection method for concrete pieces. [Background technology]

[0002] Concrete pieces may fall off from a concrete structure due to neutralization by carbon dioxide, salt damage due to the penetration of chloride ions, and other deterioration over time. To prevent such concrete pieces from falling off, a method of covering the surface of the concrete with a resin composition or a fiber sheet is known.

[0003] For example, Patent Document 1 discloses a concrete piece spalling prevention method for improving the workability of such surface protection methods, in which a primer layer is formed on the surface side of a concrete body, an elastic resin layer is then formed on the primer layer, and a reinforcing layer is then formed on the elastic resin layer, in which the reinforcing layer is formed from a specified isocyanurate compound, a specified isocyanate prepolymer, and a specified diamine compound. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-090566 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, isocyanurate compounds are being designated as hazardous or toxic substances, and polyurea and polyurethane made from isocyanurate compounds are problematic in terms of toxicity. Therefore, there is a demand for a resin composition that does not use an isocyanurate compound as a resin composition for use in a surface protection method.

[0006] In addition, urethane, which has traditionally been used as an undercoat in surface protection methods, has low strength, while epoxy has poor conformability, posing problems as a surface protection material.

[0007] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a resin composition which is less harmful and capable of forming a coating film which is excellent in strength and elongation. [Means for solving the problem]

[0008] That is, the present invention is as follows. [1] A resin composition comprising a modified silicone resin and a filler, The resin composition is cured at 23° C. and a relative humidity of 50% for 7 days, and the cured product is measured in accordance with JIS K 6251. Maximum stress is 5.0N / mm 2 That's all. The breaking strain is 100% or more, The elastic modulus is 2.0 MPa or more. Resin composition. [2] The tensile stress measured in compression mode according to JIS K 6394 using parallel plates under the conditions of a gap of 1.5 mm, strain of 0.5%, temperature of 40°C, and angular frequency of 0.1 rad / s is 25 Pa or more. The resin composition according to [1]. [3] the modified silicone resin contains a linear polymer A having two or more reactive silyl groups at each end, The content of the linear polymer A is 10 to 90 mass% based on the total amount of the modified silicone resin. The resin composition according to [1] or [2]. [4] the modified silicone resin contains a linear polymer B having one reactive silyl group at each end, The content of the linear polymer B is 10 to 90 mass% based on the total amount of the modified silicone resin. The resin composition according to any one of [1] to [3]. [5] The content of the modified silicone resin is 20 to 99 mass% based on the total amount of the resin composition. The resin composition according to any one of [1] to [4]. [6] The average particle size of the filler is 400 nm or less. The resin composition according to any one of [1] to [5]. [7] The content of the filler is 1.0 to 15% by mass based on the total amount of the resin composition. The resin composition according to any one of [1] to [6]. [8] The filler contains at least one selected from the group consisting of silica, alumina, calcium carbonate, and resin particles; The resin composition according to any one of [1] to [7]. [9] Used for surface protection of concrete pieces. The resin composition according to any one of [1] to [8].

[10] The method includes a step of forming an intermediate coating layer on a surface of a concrete structure or on a surface of another layer formed on the surface of the concrete structure using the resin composition according to any one of [1] to [9]. A method for protecting the surface of concrete pieces. Effect of the Invention

[0009] According to the present invention, it is possible to provide a resin composition which is less harmful and capable of forming a coating film having excellent strength and elongation properties. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a diagram showing tensile properties in the examples. [Diagram 2] FIG. 1 is a diagram showing an outline of a push-out test. [Diagram 3] FIG. 1 is a diagram showing the results of a push-out test in an example. [Figure 4] FIG. 2 is a diagram showing an outline of a crack follow-up test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Below, we will explain in detail the embodiment of the present invention (hereinafter referred to as the "present embodiment"). However, the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.

[0012] [Resin composition] The resin composition of the present embodiment is a resin composition containing a modified silicone resin and a filler, and when the resin composition is cured at 23°C and a relative humidity of 50% for 7 days, the cured product has a maximum stress of 5.0 N / mm when measured in accordance with JIS K 6251. 2 or more, the breaking strain is 100% or more, and the elastic modulus is 2.0 MPa or more.

[0013] (Maximum stress) The resin composition was cured at 23°C and 50% relative humidity for 7 days. The cured product had a maximum stress of 5.0 N / mm2 measured according to JIS K 6251 (hereinafter simply referred to as "maximum stress"). 2 or more, preferably 6.0 to 25 N / mm 2 More preferably, it is 7.0 to 20 N / mm 2 and more preferably 7.5 to 18 N / mm 2 and even more preferably 10 to 18 N / mm 2 It is.

[0014] (breaking strain) The resin composition is cured at 23°C and a relative humidity of 50% for 7 days, and the cured product has a breaking strain (hereinafter simply referred to as "breaking strain") measured in accordance with JIS K 6251 of 100% or more, preferably 120% to 600%, more preferably 140% to 550%, even more preferably 160% to 500%, and still more preferably 180% to 500%.

[0015] (Elasticity Modulus) The resin composition is cured at 23°C and a relative humidity of 50% for 7 days, and the cured product has an elastic modulus measured in accordance with JIS K 6251 (hereinafter simply referred to as "elastic modulus") of 2.0 MPa or more, preferably 3.0 to 35 MPa, more preferably 4.0 to 30 MPa, even more preferably 5.0 to 25 MPa, and still more preferably 6.0 to 20 MPa.

[0016] The strength and elongation of the resulting coating film are the combined effects of the maximum stress, the breaking strain, and the elastic modulus, and the maximum stress, the breaking strain, and the elastic modulus are all equal to or greater than the lower limit, so that the strength and elongation of the resulting coating film are improved. More specifically, even if the maximum stress or the elastic modulus is equal to or greater than the lower limit, if the breaking strain is poor, the cured product (coating film) breaks easily in the push-out test described in the examples, and the crack follow-up test also results in poor follow-up. Also, even if the breaking strain is equal to or greater than the lower limit and the maximum stress or the elastic modulus is poor, the cured product (coating film) breaks easily in the push-out test.

[0017] The maximum stress, breaking strain and elastic modulus can be adjusted by the type and content of modified silicone resin and filler. More specifically, by using modified silicone resin with high crosslinking density, the maximum stress and elastic modulus tend to be improved, and by using modified silicone resin with low crosslinking density and more flexible skeleton, the breaking strain tends to be improved. In this embodiment, the maximum stress, breaking strain and elastic modulus can be adjusted by using two or more modified silicone resins as described later.

[0018] The maximum stress, breaking strain and elastic modulus can be measured in accordance with JIS K 6251. In measuring the maximum stress, breaking strain and elastic modulus, the thickness of the No. 3 dumbbell is 1 mm, and the tensile speed is 100 mm / min.

[0019] (Extensile stress) The tensile stress (hereinafter simply referred to as "yield tensile stress") measured in a compression mode in accordance with JIS K 6394 using parallel plates under conditions of a gap of 1.5 mm, a strain of 0.5%, a temperature of 40°C, and an angular frequency of 0.1 rad / s is preferably 25 Pa or more, more preferably 30 to 800 Pa, even more preferably 35 to 700 Pa, and still more preferably 40 to 600 Pa.

[0020] The composition of the present embodiment can be applied to places where dripping is likely to occur due to gravity, such as walls and ceilings. The condition of an angular frequency of 0.1 rad / s corresponds to the speed at which dripping begins to occur when the composition is applied to, for example, a ceiling, and dripping can be prevented by having a yield elongation stress of 25 Pa or more measured under the above conditions. Therefore, in addition to improving the handling properties, dripping is suppressed, and a uniform coating film with reduced variations in strength and elongation can be obtained.

[0021] (Modified silicone resin) The modified silicone resin in the present embodiment refers to a polymer having a reactive silyl group, and includes those in which a reactive silyl group is added to a polymer that is the main chain. The modified silicone resin may be used alone or in combination of two or more kinds.

[0022] The polymer to which the reactive silyl group is added is not particularly limited, but examples thereof include polyether polymers such as polyoxyethylene, polyoxypropylene, and polyoxybutylene; aliphatic hydrocarbon polymers such as polyisoprene, polyisobutylene, and polybutadiene; acrylic polymers such as poly(meth)acrylic acid and poly(meth)acrylate; and polyester polymers.

[0023] Among these, polyether-based polymers are preferred. Among polyether-based polymers, polyoxyalkylenes are more preferred. Among polyoxyalkylenes, polyoxypropylene is more preferred. By using such a polymer as the main chain, the flexibility of the main chain is high, so that the breaking strain and elastic modulus are further improved, and the extensibility of the obtained coating film tends to be further improved.

[0024] The polymer skeleton may be linear or branched, but is preferably linear. By using such a modified silicone resin, excessive increase in crosslink density is suppressed, and the breaking strain and elastic modulus are further improved, so that the extensibility of the resulting coating film tends to be further improved.

[0025] The reactive silyl group is not particularly limited, and examples thereof include an addition reactive silyl group, a condensation reactive silyl group, and a hydrolyzable silyl group. More specifically, examples thereof include a group in which a reactive group such as a hydrogen atom, a hydroxyl group, an alkoxy group, a halogen atom, an acyloxy group, an alkenyloxy group, an amide group, an oxime group, a ketoximate group, an amide group, an acid amide group, a mercapto group, or an aminooxy group is bonded to a silicon atom.

[0026] Such reactive silyl groups are not particularly limited, but examples thereof include those represented by the following formula (1): -(SiOX b R 2-b ) n -SiX a R 3-a ... (1) (In the formula, each R independently represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms; each X independently represents a hydrogen atom, a hydroxyl group, an alkoxy group, a halogen atom, an acyloxy group, an alkenyloxy group, an amide group, an oxime group, a ketoximate group, an amide group, an acid amide group, a mercapto group, or an aminooxy group; a represents an integer of 1 to 3, b represents an integer of 0 to 2, and n represents an integer of 0 to 10.)

[0027] Specific examples of reactive silyl groups are not particularly limited, but include alkoxysilyl groups such as trimethoxysilyl group, dimethoxymethylsilyl group, dimethylmethoxysilyl group, triethoxysilyl group, diethoxymethylsilyl group, dimethylethoxysilyl group, dimethoxyphenylsilyl group, diphenylmethoxysilyl group, diethoxyphenylsilyl group, and diphenylethoxysilyl group; and polymerized reactive silyl groups such as dialkyl silicone, alkylalkoxysilicone, dialkoxysilicone, diphenyl silicone, and alkoxyphenyl silicone, which are end-bonded with these alkoxysilyl groups. Among the reactive silyl groups, dimethoxymethylsilyl group is preferred.

[0028] In addition, the bonding position of the reactive silyl group in the polymer is not particularly limited, but can be, for example, the end of the main chain of the polymer, a side chain, or both the end and the side chain.Among these, a modified silicone resin having a reactive silyl group at the end of the main chain of the polymer is preferred.By using such a modified silicone resin, the distance between crosslinking points and the number of crosslinking points can be more easily controlled, and the maximum stress, breaking strain, and elastic modulus can be more suitably adjusted, so that the strength and elongation of the obtained coating film can be further improved.

[0029] The mode of bonding of the reactive silyl group to the terminal of the polymer is not particularly limited, and the reactive silyl group (-SiX) can be bonded by any linker L depending on the method for modifying the terminal of the polymer with the reactive silyl group. a R 3-a ) can be bonded to the end of the polymer. Here, the linker L can be a portion that connects the terminal atom of the repeating unit of the polymer to the silicon atom of the reactive silyl group represented by formula (1). For example, when the polymer is polyoxyethylene, the terminal atoms of the repeating unit are an oxygen atom at one end and a carbon atom at the other end. In addition, when the polymer is an acrylic polymer and an initiator is added to the end of the polymer, the initiator portion is included in the linker L.

[0030] Such a linker L is not particularly limited, but examples thereof include linking groups that may have a urethane bond, a urea bond, an ester bond, an amide bond, an ether bond, and a siloxane bond. Examples of such linking groups include groups represented by the following formulas (a) to (i). [ka] (In the formula, R 1 is a group bonded to the end of a polymer, and represents a single bond or a hydrocarbon group having 1 to 10 carbon atoms; R 2 are groups bonded to reactive silyl groups, each independently representing a single bond or a hydrocarbon group having 1 to 10 carbon atoms, each independently representing a urethane bond, a urea bond, an ester bond, an amide bond, an ether bond, or a siloxane bond, R 3 each independently represents a hydrocarbon group having 1 to 10 carbon atoms.

[0031] Formulae (a) to (c) are linear linkers, formulae (d) to (f) are two-branched linkers, and formulae (g) to (i) are three-branched linkers. However, the linking group is not limited to the above, and a linear linking group having two to five branches can be used. The total number of carbon atoms in the linking group is preferably 1 to 30, more preferably 1 to 20, and even more preferably 1 to 10. In formula (a), R 1 also bonds to reactive silyl groups.

[0032] The number of reactive silyl groups bonded to one end of the polymer is preferably 1 to 5. Among these, the modified silicone resin is preferably a modified silicone resin having two or more reactive silyl groups at each end (hereinafter also referred to as "linear polymer A"), a modified silicone resin having one reactive silyl group at each end (hereinafter also referred to as "linear polymer B"), or a combination of these. By using a combination of modified silicone resins having different numbers of reactive silyl groups in this way, the maximum stress, breaking strain, and elastic modulus can be more suitably adjusted, and the strength and elongation of the resulting coating film can be further improved.

[0033] A modified silicone resin having at least two silicon atoms bonded to alkoxy groups at each end is preferred as the linear polymer A. By using such a linear polymer A, the crosslink density of the cured product is improved, which leads to further improvements in the maximum stress and elastic modulus, and the strength of the resulting coating film tends to be further improved.

[0034] The viscosity of the linear polymer A at 25°C is preferably 100 to 7000 mPas, more preferably 500 to 5000 mPas, and even more preferably 1000 to 3000 mPas. Generally, the smaller the molecular weight, the smaller the viscosity tends to be. However, by having the viscosity within the above range, the crosslink density of the cured product is improved, and the maximum stress and elastic modulus are further improved, and the strength of the resulting coating film tends to be further improved. The viscosity in this embodiment can be measured by a conventional method using a Brookfield viscometer (B-type rotational viscometer). The viscosity in this embodiment is measured under conditions of 25°C and a rotation speed of 10 rpm.

[0035] The linear polymer A preferably uses a linking group having a siloxane bond as a linker. By using such a modified silicone resin, the crosslink density of the cured product is improved, and the maximum stress and elastic modulus are improved, and the strength of the resulting coating film tends to be improved. In addition, the linear polymer A may or may not have a flexible group such as a urethane bond. For example, by having a flexible group such as a urethane bond, the breaking strain of the cured product is improved, and the extensibility of the resulting coating film tends to be improved, and by not having a flexible group such as a urethane bond, isocyanate, which is a raw material for forming a urethane bond, is less likely to be mixed into the resin composition, so a safer resin composition can be obtained.

[0036] The content of the modified silicone resin having two or more reactive silyl groups at each end, such as the linear polymer A, is preferably 10 to 90 mass%, more preferably 20 to 85 mass%, and even more preferably 30 to 85 mass%, based on the total amount of the modified silicone resin. By having the content of the modified silicone resin having two or more reactive silyl groups at each end within the above range, the maximum stress and elastic modulus are further improved, and the strength of the obtained coating film tends to be further improved.

[0037] In addition, a modified silicone resin having one silicon atom bonded to an alkoxy group at each end is preferred as the linear polymer B. Since such a linear polymer B has a relatively low crosslink density, the breaking strain of the cured product is improved, and the extensibility of the resulting coating film tends to be improved.

[0038] The linear polymer B may have a flexible group such as a urethane bond. By using such a modified silicone resin, the breaking strain of the cured product is improved, and the extensibility of the resulting coating film tends to be improved.

[0039] The viscosity of the linear polymer B at 25° C. is preferably 7500 to 40000 mPas, more preferably 10000 to 45000 mPas, and even more preferably 20000 to 50000 mPas. Generally, the viscosity tends to increase as the molecular weight increases, but by having the viscosity within the above range, the crosslink density of the cured product decreases, which improves the breaking strain and tends to improve the extensibility of the resulting coating film.

[0040] The content of the modified silicone resin having one reactive silyl group at each end, such as the linear polymer B, is preferably 10 to 90 mass%, more preferably 15 to 80 mass%, and even more preferably 15 to 70 mass%, based on the total amount of the modified silicone resin. By having the content of the modified silicone resin having one reactive silyl group at each end within the above range, the breaking strain of the cured product is improved, and the extensibility of the obtained coating film tends to be improved.

[0041] The content of the modified silicone resin is preferably 20 to 99 mass%, more preferably 25 to 99 mass%, and further preferably 30 to 99 mass%, based on the total amount of the resin composition. By having the content of the modified silicone resin within the above range, the maximum stress, breaking strain, and elastic modulus are further improved, and the strength and extensibility of the obtained coating film tend to be further improved.

[0042] (Filler) The filler is not particularly limited, and examples thereof include inorganic fillers and organic fillers. The fillers may be used alone or in combination of two or more kinds.

[0043] The inorganic filler is not particularly limited, but examples thereof include silica; oxides such as alumina, titanium oxide, and magnesium oxide; carbonates such as calcium carbonate and magnesium carbonate; hydroxides such as aluminum hydroxide and magnesium hydroxide; and inorganic fibers such as glass fibers.

[0044] The organic filler is not particularly limited, but examples thereof include resin particles such as acrylic beads; and organic fibers such as cellulose fibers and synthetic resin fibers.

[0045] Among these, it is preferable to use one or more selected from the group consisting of silica, alumina, calcium carbonate, and resin particles. By using such a filler, the yield elongation stress is further improved and dripping tends to be suppressed.

[0046] The average particle size of the filler is preferably 400 nm or less, more preferably 1 to 200 nm, even more preferably 1 to 100 nm, and even more preferably 1 to 50 nm. By having the average particle size within the above range, the yield elongation stress is further improved and dripping tends to be suppressed. In this embodiment, the average particle size refers to the primary particle size on a volume basis. The primary particle size can be measured by a laser diffraction scattering method.

[0047] The content of the filler is preferably 1.0 to 15 mass%, more preferably 1.5 to 10 mass%, and further preferably 2.0 to 8.0 mass%, based on the total amount of the resin composition. When the content of the filler is within the above range, the yield elongation stress is further improved and dripping tends to be suppressed.

[0048] (Other Ingredients) The resin composition of the present embodiment may contain other components in addition to the modified silicone resin and the filler. The other components are not particularly limited, but may include, for example, silicone resins other than the modified silicone, silane coupling agents, curing catalysts, organic pigments, inorganic pigments, ultraviolet absorbers, and light stabilizers.

[0049] The silicone resin is not particularly limited, but examples thereof include polydimethylsiloxane, polymethylphenylsiloxane, polydiphenylsiloxane, and copolymers or modified products thereof. Examples of the modified products include those in which a part of the methyl group or phenyl group is modified with an alkyl, aralkyl, fluoroalkyl, polyether, amino, acrylic, or epoxy group.

[0050] When a silicone resin is contained, the content of the silicone resin is preferably 45 to 75 mass %, more preferably 50 to 70 mass %, and further preferably 55 to 65 mass %, based on the total amount of the resin composition.

[0051] Examples of silane coupling agents include, but are not limited to, aminosilane-based compounds such as 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane; epoxysilane-based compounds such as γ-glycidoxypropyltrimethoxysilane; vinylsilane-based compounds such as γ-(meth)acryloxypropyltrimethoxysilane; cationic silane-based compounds such as N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride; and phenylsilane-based compounds.

[0052] The silane coupling agent can function as a curing agent. When the silane coupling agent is contained, the content of the silane coupling agent is preferably 0.1 to 7.5 mass%, more preferably 0.5 to 5.0 mass%, and further preferably 1.0 to 3.0 mass%, based on the total amount of the resin composition.

[0053] The curing catalyst is not particularly limited as long as it catalyzes the reaction of a reactive silyl group, and examples thereof include tin-based catalysts, titanium-based catalysts, aluminum-based catalysts, zinc-based catalysts, iron-based catalysts, and phosphorus-based catalysts.

[0054] The ultraviolet absorbing agent (UVA) is not particularly limited, but examples thereof include benzotriazole-based compounds, hydroxyphenyltriazine-based compounds, and polymers containing benzotriazole or benzophenone.

[0055] The light stabilizer (HALS) is not particularly limited, but examples thereof include N-OR type hindered amine compounds, NR type hindered amine compounds, and NH type hindered amine compounds. Here, R represents a hydrocarbon group, and N-OR type and NR type refer to those in which an OR group and an R group are bonded to the nitrogen atom of a piperidyl skeleton. In addition, NH type refers to those in which a hydrogen atom is bonded to the nitrogen atom of a piperidyl skeleton.

[0056] [Application] The resin composition of the present embodiment can be suitably used for reinforcing, repairing, or bonding an adherend, and is particularly preferably used in a surface protection method for concrete pieces. The surface protection method in the present embodiment includes a spalling prevention method performed for the purpose of preventing concrete from spalling, and a protection method performed for the purpose of blocking deterioration factors such as salt, oxygen, moisture, or light, and the composition of the present embodiment can be suitably used in either method. Among these, the resin composition of the present embodiment, which can form a coating film excellent in strength and elongation, can be suitably used in the spalling prevention method.

[0057] In particular, the resin composition of the present embodiment is preferably used as an intermediate layer in a surface protection method for concrete pieces. The intermediate layer is a layer that is responsible for the mechanical properties of the coating material in the surface protection method for concrete pieces, and is generally formed on a primer layer formed on the surface of a concrete skeleton. By using it for such purposes, concrete can be reinforced or repaired without using toxic substances such as isocyanates.

[0058] Furthermore, since the resin composition of this embodiment has an excellent balance between strength and elongation, it can also show good results in push-out tests and crack follow-up tests, making it possible to realize a more reliable anti-peeling treatment.

[0059] [Concrete piece surface protection method] The concrete piece surface protection method of the present embodiment includes a step of forming an intermediate coat layer on the surface of a concrete structure or on the surface of another layer formed on the surface of the concrete structure using the above resin composition. In addition, the concrete piece surface protection method of the present embodiment may, if necessary, form a primer layer as another layer on the surface of the concrete structure, or may further form a top coat layer on the surface of the intermediate coat layer.

[0060] By forming the primer layer, the adhesion between the concrete structure and the intermediate coating layer tends to be improved. The resin contained in the primer layer is not particularly limited, but examples thereof include acrylic resin, olefin resin, vinyl acetate resin, urethane resin, epoxy resin, aminated epoxy resin, urea resin, silicone resin, and modified resins thereof.

[0061] In addition, since the resin composition of the present embodiment has excellent adhesion to concrete structures, it can also be suitably used in surface protection methods that do not require the formation of a primer layer.

[0062] In addition, by forming a topcoat layer, weather resistance tends to be further improved. The resin contained in the topcoat layer is not particularly limited, but examples thereof include fluorine resin, acrylic resin, acrylic silicone resin, acrylic urethane resin, urethane resin, olefin resin, vinyl acetate resin, ethylene vinyl acetate copolymer resin, silicone resin, and modified resins thereof.

[0063] The method for forming each layer is not particularly limited, but for example, a method of coating the resin composition that forms each layer and then drying at room temperature or using a drying device can be mentioned. In addition, when laminating layers, the underlying layer is dried before the next layer is formed. The drying time varies depending on the coating environment conditions, etc., but can be, for example, one day or more. EXAMPLES

[0064] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0065] Example 1 80 parts by weight of modified silicone resin A (manufactured by Asahi Kasei Wacker Silicone Co., Ltd., product name: XB502, viscosity at 25°C: 2000mPas, modified silicone resin having two or more silicon atoms bonded to methoxy groups at each end, polyoxypropylene structure as polyether polymer, dimethoxymethylsilyl group as reactive silyl group), 20 parts by weight of modified silicone resin B (manufactured by Asahi Kasei Wacker Silicone Co., Ltd., product name: E30, viscosity at 25°C: 30000mPas, modified silicone resin having one silicon atom bonded to methoxy groups at each end, polyoxypropylene structure as polyether polymer, dimethoxymethylsilyl group as reactive silyl group), and 6 parts by weight of silica (manufactured by Asahi Kasei Wacker Silicone Co., Ltd., product name: H18, average particle size: 10nm) were added and stirred for 5 minutes. Furthermore, 2 parts by weight of 3-aminopropyltrimethoxysilane was added and stirred for 5 minutes to prepare a resin composition.

[0066] Example 2 A resin composition was prepared in the same manner as in Example 1, except that the amount of modified silicone resin A used was 50 parts by weight and the amount of modified silicone resin B used was 50 parts by weight.

[0067] Example 3 A resin composition was prepared in the same manner as in Example 1, except that the amount of silica used was 3 parts by weight.

[0068] Comparative Example 1 A resin composition was prepared in the same manner as in Example 1, except that the amount of modified silicone resin A used was 100 parts by weight and that modified silicone resin B was not used.

[0069] Comparative Example 2 A resin composition was prepared in the same manner as in Example 1, except that the amount of modified silicone resin A used was 20 parts by weight and the amount of modified silicone resin B used was 80 parts by weight.

[0070] Comparative Example 3 A resin composition was prepared in the same manner as in Example 1, except that silica was not used.

[0071] [Measurement of maximum stress, breaking strain and elastic modulus] The resin composition obtained as described above was molded into a sheet having a thickness of 1 mm, and left to stand for 7 days under an environment of 23°C and 50% relative humidity to obtain a sheet-like cured product. This was punched into a No. 3 dumbbell shape and used for measuring the maximum stress, breaking strain, and elastic modulus, which will be described later. The maximum stress, breaking strain, and elastic modulus were measured in accordance with JIS K 6251. In the above measurements, the No. 3 dumbbell had a thickness of 1 mm and the tensile speed was 100 mm / min. The results are shown below. The tensile test results are shown in FIG. 1.

[0072] [Table 1]

[0073] [Push-out test] In accordance with JSCE K 511, a test substrate having the shape shown in FIG. 2(a) was prepared, and the resin composition prepared as described above was applied to the surface of the test substrate in an amount of 1.0 [kg / m 2 The test substrate was coated with the following composition. The substrate was then left to stand at 23°C and 50% relative humidity for 7 days to harden the resin composition and produce a coating film. The test substrate had a cylindrical hole with a diameter of 10 mm and a depth of 55 mm on the side opposite to the side on which the coating film was produced.

[0074] The push-out test was conducted in accordance with JSCE K 533. Specifically, as shown in Figure 2(b), a cylindrical core surrounded by drilled holes was loaded from the non-coated surface toward the coated surface, and the loading was temporarily stopped when the displacement reached 10 mm. During this time, the change over time in the load (kN) applied when loading at 5 mm / min was monitored, and the peeled area when the displacement reached 10 mm was marked. This was repeated every 10 mm of displacement, and loading was continued until the coating broke.

[0075] The loading rate was 1 mm / min until the remaining core was destroyed, and then 5 mm / min after the remaining core was destroyed.

[0076] Figure 3 shows the change in load (kN) over time in the push-out test. The same push-out test was performed three times, and Table 2 shows the average values ​​of the measured maximum load and maximum displacement. As shown in Table 2 and Figure 3, in Comparative Example 1, which has a relatively high maximum stress and elastic modulus and a low breaking strain, and in Comparative Example 2, which has a relatively high breaking strain and a low maximum stress and elastic modulus, it was found that the cured product (coating film) easily broke in the push-out test. In contrast, in Examples 1 and 2, it was found that the maximum stress, elastic modulus, and breaking strain were greater than or equal to the predetermined values, and thus the maximum load and maximum displacement were much better than those in Comparative Examples 1 and 2.

[0077] [Table 2]

[0078] [Crack follow-up test] In accordance with JSCE K 511, a test substrate having the shape shown in FIG. 4(a) was prepared, and the resin composition prepared as described above was applied to the surface of the test substrate in an amount of 1.5 [kg / m 2 The test substrate was left to stand at 23°C and 50% relative humidity for 7 days to harden the resin composition and produce a coating film. The test substrate had a cut surface in the center, and the coating film was formed so as to cross the cut surface.

[0079] The crack follow-up test was conducted in accordance with JSCE-K 532. Specifically, as shown in Figure 4(b), the test substrate was pulled in the longitudinal direction by a load cell (capacity 2 kN) and the test was continued until the coating film broke. The displacement at which the coating film broke was then measured.

[0080] This crack-following test was performed three times, and the average value of the measured displacement is shown in Table 3. As shown in Table 3, in Comparative Example 1, in which the maximum stress and elastic modulus were relatively high and the breaking strain was low, it was found that the cured product (coating film) broke easily in the crack-following test. In contrast, in Examples 1 and 2, it was found that the maximum stress, elastic modulus, and breaking strain were equal to or greater than the predetermined values, and thus the displacement was much improved compared to Comparative Example 1.

[0081] [Table 3]

[0082] [Evaluation of dripping] First, using a dynamic viscoelasticity measuring device (manufactured by TA Instruments, device name: RSA-G2), the yield elongation stress was measured in compression mode in accordance with JIS K 6394 under conditions of a gap of 1.5 mm, strain of 0.5%, temperature of 40°C, and angular frequency of 0.1 rad / s.

[0083] Next, a test substrate was prepared in accordance with JSCE K 511, and the test substrate was held so that the surface direction of the test substrate was parallel to the ground. The resin composition prepared as described above was applied to the side (lower surface) of the test substrate opposite the surface. In this state, the substrate was left to stand at 23°C and a relative humidity of 50% for 24 hours, and it was confirmed whether dripping occurred or not.

[0084] The results are shown in Table 4. The samples that did not drip were evaluated as ◯, and the samples that dripped were evaluated as ×. As shown in Table 4, it was found that the occurrence of dripping correlated well with the yield elongation stress.

[0085] [Table 4] [Industrial Applicability]

[0086] INDUSTRIAL APPLICABILITY The present invention has industrial applicability as a resin composition used in a surface protection method for concrete pieces, or for other reinforcement, repair, adhesion, and the like.

Claims

1. A resin composition comprising a modified silicone resin and a filler, The resin composition is cured at 23° C. and 50% relative humidity for 7 days, and the cured product is measured in accordance with JIS K 6251. Maximum stress is 5.0 N / mm 2 That's all. The breaking strain is 100% or more, The elastic modulus is 2.0 MPa or more. Resin composition.

2. The elongation stress measured in a compression mode in accordance with JIS K 6394 using parallel plates under the conditions of a gap of 1.5 mm, a strain of 0.5%, a temperature of 40° C., and an angular frequency of 0.1 rad / s is 25 Pa or more. The resin composition according to claim 1.

3. the modified silicone resin comprises a linear polymer A having two or more reactive silyl groups at each of both ends, The content of the linear polymer A is 10 to 90 mass% based on the total amount of the modified silicone resin. The resin composition according to claim 1 or 2.

4. the modified silicone resin contains a linear polymer B having one reactive silyl group at each end, The content of the linear polymer B is 10 to 90 mass% based on the total amount of the modified silicone resin. The resin composition according to any one of claims 1 to 3.

5. The content of the modified silicone resin is 20 to 99% by mass based on the total amount of the resin composition. The resin composition according to any one of claims 1 to 4.

6. The average particle size of the filler is 400 nm or less. The resin composition according to any one of claims 1 to 5.

7. The content of the filler is 1.0 to 15 mass% based on the total amount of the resin composition. The resin composition according to any one of claims 1 to 6.

8. The filler contains at least one selected from the group consisting of silica, alumina, calcium carbonate, and resin particles; The resin composition according to any one of claims 1 to 7.

9. Used for surface protection of concrete pieces. The resin composition according to any one of claims 1 to 8.

10. The method includes a step of forming an intermediate layer on a surface of a concrete structure or on a surface of another layer formed on the surface of the concrete structure using the resin composition according to any one of claims 1 to 9. A method for protecting the surface of concrete pieces.

Citation Information

Patent Citations

  • Composition containing organic polymer having reactive silicone group

    JP2009120719A

  • Primer composition

    JP2014159601A

  • Moisture-curing silylated polymer composition with improved adhesion to concrete

    JP2014510816A

  • Curable composition

    JP2016210840A

  • Curable composition

    JP2017066349A